2013
DOI: 10.1093/cid/cis1010
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Protection of Adults From Rotavirus by Pediatric Rotavirus Vaccination

Abstract: Pediatric rotavirus vaccination correlated with a relative decline of almost 50% in rotavirus identified from adult BSC during the peak rotavirus season, suggesting that pediatric rotavirus vaccination protects adults from rotavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 30 publications
3
57
0
3
Order By: Relevance
“…In the United States, following vaccine implementation in 2006, rotavirus hospitalizations have declined 60-83% in children <5 years of age and all-cause diarrhea hospitalizations decreased by 29-50% compared with pre-vaccine years [24][25][26][27][28][29]. In addition to providing direct protection to vaccinated infants, indirect protection, likely from reduced rotavirus transmission in the community, has also been observed among children too old to have received the vaccine, as well as among adults in the United States [30][31][32]. One study estimated that over two seasons from 2008-2009, an estimated total of 60,000-80,000 diarrheal hospitalizations were prevented in young children resulting in a medical cost savings of $240-$280 million, and these saving have continued through subsequent rotavirus seasons [26,33].…”
Section: Post-licensure Datamentioning
confidence: 99%
“…In the United States, following vaccine implementation in 2006, rotavirus hospitalizations have declined 60-83% in children <5 years of age and all-cause diarrhea hospitalizations decreased by 29-50% compared with pre-vaccine years [24][25][26][27][28][29]. In addition to providing direct protection to vaccinated infants, indirect protection, likely from reduced rotavirus transmission in the community, has also been observed among children too old to have received the vaccine, as well as among adults in the United States [30][31][32]. One study estimated that over two seasons from 2008-2009, an estimated total of 60,000-80,000 diarrheal hospitalizations were prevented in young children resulting in a medical cost savings of $240-$280 million, and these saving have continued through subsequent rotavirus seasons [26,33].…”
Section: Post-licensure Datamentioning
confidence: 99%
“…In children from Caxias do Sul, the RV vaccine coverage reached 90.3% and increased further until 2013. The research conducted by Anderson et al [25] showed that the vaccination of children against RV is correlated with an almost 50% reduction in RV among adults [25]. Other reports reviewed the number of registered cases of nonspecific gastroenteritis caused by RV [26].…”
Section: Discussionmentioning
confidence: 99%
“…Сокращение числа обращений в отделения неотлож-ной терапии по причине ОГЭ выявлено среди женщин 20-29 лет и детей в возрасте 5-19 лет [68]. В целом, в США на фоне широкой вакцинации младенцев упало количество обращений взрослых пациентов по пово-ду РВГЭ (на 48,4%), что, несомненно, свидетельствует о формировании популяционного иммунитета в ходе иммунизации ПВРВВ [69].…”
Section: вопросы современной педиатрииunclassified